2018
DOI: 10.3390/nu10070857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Strawberry Genotype, Cultivation and Processing on the Fra a 1 Allergen Content

Abstract: Birch pollen allergic patients show cross-reactivity to vegetables and fruits, including strawberries (Fragaria × ananassa). The objective of this study was to quantify the level of the Fra a 1 protein, a Bet v 1-homologous protein in strawberry fruits by a newly developed ELISA, and determine the effect of genotype, cultivation and food processing on the allergen amount. An indirect competitive ELISA using a specific polyclonal anti-Fra a 1.02 antibody was established and revealed high variability in Fra a 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…From these results, we concluded that fruit color is not indicative of allergenicity related to Fra a 1.01. This finding was consistent with those of two previous studies on European varieties harvested in spring (Franz-Oberdorf et al, 2017;Kurze et al, 2018). One of the major reasons for no interaction between Fra a 1 expression and fruit color is the genetic variation in the flavonoid biosynthesis pathway in each white cultivar, that is, different mutations in an enzyme like phenylalanine ammonia-lyase (PAL) and/or dihydrokaempferol 4reductase (DFR), a transcription factor like MYB, or a binding protein to metabolic intermediates like Fra a 1.…”
Section: Rough Screening Of Cultivarssupporting
confidence: 94%
See 2 more Smart Citations
“…From these results, we concluded that fruit color is not indicative of allergenicity related to Fra a 1.01. This finding was consistent with those of two previous studies on European varieties harvested in spring (Franz-Oberdorf et al, 2017;Kurze et al, 2018). One of the major reasons for no interaction between Fra a 1 expression and fruit color is the genetic variation in the flavonoid biosynthesis pathway in each white cultivar, that is, different mutations in an enzyme like phenylalanine ammonia-lyase (PAL) and/or dihydrokaempferol 4reductase (DFR), a transcription factor like MYB, or a binding protein to metabolic intermediates like Fra a 1.…”
Section: Rough Screening Of Cultivarssupporting
confidence: 94%
“…The pattern of change was either up-or down-regulation in each genotype. In Germany, there was no significant annual change in Fra a 1 protein levels among fresh fruits of a red cultivar (Kurze et al, 2018). To our knowledge, this is the first report that Fra a 1 concentrations in strawberries differ during the harvest season and among months.…”
Section: Seasonal Variation In Fra a 1 Transcript Levels And Fra A 1 mentioning
confidence: 58%
See 1 more Smart Citation
“…The prevalence of food allergies ranges from 2-10% in the US depending on the state [ 9 ]. Although less common, allergies to certain fruits such as strawberries [ 10 ] drive the population to avoid them. Many fruits, for example peaches, apples, and apricots, lead to irritation in the digestive tract due to the high fructose content, which is a concern for people suffering from irritable bowel syndrome (IBS) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several external stimuli induce Fra a 1 expression, including UV-C radiation, chitosan treatments, and achene removal (Ishibashi et al, 2017;Petriccione et al, 2017;Severo et al, 2015). Differences in Fra a 1 expression levels in varieties have been reported in some cultivation areas (Alm et al, 2007;Franz-Oberdorf et al, 2016); however, differences, as assessed by Fra a 1 protein accumulation levels, have not been documented in various production areas, including Japan (Franz-Oberdorf et al, 2017;Ishibashi et al, 2019b;Kurze et al, 2018).…”
Section: Introductionmentioning
confidence: 99%